The Influence of the Problem Based Learning Model Based on the STEM Approach on Students' Higher Order Thinking Skills (HOTS) in Acid-Base Material. - Novita Marito Pangaribuan; Murniaty Simorangkir (Universitas Lampung, 2026)
His study aims to investigate the influence of the problem based learning model based on the stem approach on students' higher order thinking skills (hots) in acid-base material. The research employed a quasi-experimental method with a pretest-posttest control group design. The population consisted of five grade XI classes at SMA Negeri 17 Medan. The sample was selected through random sampling, resulting in two classes: class XI E as the experimental group and class XI D as the control group. Data were analyzed using hypothesis testing with a one-tailed t-test and N-gain analysis. Based on the analysis, the results of the hypothesis testing showed that tcount > ttable (4.736 > 1.997. Furthermore, the N-gain score for the experimental group (0.75) fell into the high category, while the control group (0.66) was in the moderate category. Consequently, it can be concluded that the implementation of the STEM-based Problem-Based Learning model has a significant effect on enhancing students' higher-order thinking skills in acid-base concepts.